Influence of Grape Heterogeneity on Berry Quality Traits in Table Grapes A Study on the ‘Alphonse Lavallée’ Variety - Seda Sucu; Neval Topcu Altıncı (Turkish Journal of Agriculture: Food Science and Technology)
The study, conducted in 2023 at the vineyard of the Agricultural Research and Application Center of Tokat Gaziosmanpaşa University, focused on the Alphonse Lavallée grape variety, a significant cultivar among table grapes. The research aimed to assess the impact of berry density on various quality parameters. Grape berries were selected across five different density categories (Y0-Y4), including a control group, to evaluate their physical characteristics (including width, length, weight, firmness, and skin color), chemical properties (pH, total titratable acidity, and soluble solids content), and phytochemical attributes (encompassing total phenol content, total antioxidant capacity, and total monomeric anthocyanin levels). The findings revealed that critical quality indicators—namely, soluble solids content, pH, total antioxidant capacity, and total monomeric anthocyanin—were maximized under the Y4 treatment. In contrast, the highest total phenol content was recorded in the Y2 and Y3 treatments. These results underscore the importance of berry density and berry/skin volume as key determinants of grape berry quality. The study contributes valuable insights into the role of these factors in enhancing the overall quality of table grapes, particularly in the context of the Alphonse Lavallée variety.